La primavera árabe: ¿una cuarta ola de democratización? - Priego Moreno, Alberto (UNISCI Discussion Papers, 2011)
In early 2011 the Arab countries of Northern Africa and the Middle East have been the scenario of continuous demonstrations. They were aimed at complaining against the authoritarian regimes which have been in power for more than 40 years now. Those demonstrations may constitute the beginning of a number of transition processes with common characteristics which might be explained through the concept of “Waves of Democratization” developed by Samuel Huntington. Although we cannot make predictions for the future, we can already claim that we are witnessing the Fourth Wave of Democratization.
Keywords: Waves of democratization; Middle East; Northern Africa; Revolution